Cellulose Nanowhiskers Extracted from Tempo-Oxidized Curaua Fibers. Issue 9 (1st September 2020) - Motta Neves, Roberta; Silveira Lopes, Kirk; Zimmermann, Matheus G.V.; Poletto, Matheus; Zattera, Ademir J.
ABSTRACT: The objective of this study was to obtain nanowhiskers from bleached and milled curaua fibers. Nanowhiskers were obtained via a TEMPO system. TEM micrographies proved the fibers were obtained. FTIR analysis showed characteristic peaks of the oxidation products for the samples submitted to the treatment, suggesting that the it was effective for cellulose. The results show that the TEMPO method increased crystallinity and decreased the degree of polymerization. As for thermal stability, the nanowhiskers were more thermally stable than the other samples. Based on our findings, the use of nanowhiskers may be suitable for a variety of applications, such as the production of nanocomposites.